Earthquake Disaster Simulation on Increasing Knowledge and Preparedness Attitudes of Elementary School Students in Padang City - Putri, Salsabil Syah; Tasman, Tasman; Suryarinilsih, Yosi; Rachmadanur, N.; Metti, Elvia (Jurnal Keperawatan, 2024)
The earthquake in West Sumatra in 2009 caused 1,195 people to die, where the majority of victims were the elderly and children. The factor that causes the large number of fatalities during earthquake disasters is the lack of knowledge and attitudes of the community and children regarding earthquake disaster management preparedness. This research aims to determine the effect of earthquake simulation on increasing knowledge and attitudes about earthquake disaster preparedness among elementary school students in Padang City. The research method uses Quasi-experimental with One Group Pre test and Post design, the research location is Lubuk Lintah State Elementary School 21. The population is 80 grade 5 elementary school students with 44 samples taken by proportionate random sampling. The data collection technique uses a questionnaire. The earthquake disaster simulation educational intervention was carried out twice in one meeting for 2x120 minutes. Data analysis used the Paired T-dependent test. The research results showed that there was an effect of increasing knowledge and attitudes before and after being given an earthquake simulation to elementary school students with P-value = 0.000. The research conclusions show that earthquake simulations can be used to increase knowledge and attitudes about earthquake disaster preparedness among elementary school students. If earthquake simulation is used as an activity program in schools, it can make students resilient to disasters.